PENGARUH PERILAKU KONSUMTIF DAN COUNTRY OF ORIGIN TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK (Studi pada Wanita Bekerja di Wilayah Surabaya) - INDAR RAHMANI, PUTRI (Jurnal Ilmu Manajemen (JIM), 2019)
Abstract The rapid development of the cosmetics industry in this century affects the way women work about the true meaning of beauty which is required to look beautiful and attractive while working. this gives rise to working women tend to behave consumptively in the purchase of cosmetics and always consider where the country of origin of cosmetics used or prioritizes "Made In ...". The sampling technique used is non probability sampling with judgmental sampling method. The sample used was 220 respondents. Respondents in this study were working women aged 25-35 years who had bought and used maybelline, revlon, and NYX brand cosmetics. The data analysis technique uses multiple linear regression with a measurement scale using a Likert scale. The results of this study indicate that the consumptive behavior variable has a higher influence than the country of origin, so it can be concluded that cosmetic purchasing decisions in working women are much influenced by consumptive behaviors that are more concerned with personality. Keywords: consumptive behaviour; country of origin; purchasing decision.